Same-day colon capsule endoscopy is a viable means to assess unexplored colonic segments after incomplete colonoscopy in selected patients. Issue 10 (December 2018) - Hussey, Mary; Holleran, Grainne; Stack, Roisin; Moran, Neil; Tersaruolo, Claudio; McNamara, Deirdre
Background: Same-day colon capsule endoscopy (CCE) immediately following incomplete optical colonoscopy (OC) would have a number of advantages for patients, while also presenting unique procedural challenges including the effect of sedation on capsule propulsion and patient tolerance of protracted preparation and fasting. Aim: The aim of this article is to prospectively assess the efficacy of same-day CCE after incomplete OC in an unselected patient cohort. Methods: This was an observational, prospective, single-centre study of CCE post-incomplete colonoscopies. Patients with an incomplete OC for any reason other than obstruction or inadequate bowel preparation were recruited. CCE was performed after a minimum of a one-hour fast. Once the patient was fully alert, intravenous metoclopramide was administered after capsule ingestion when possible, and a standard CCE booster protocol was then followed. Relevant clinical information was recorded. CCE completion rates, findings and their impact, and adverse events were noted. Results: Fifty patients were recruited, mean age = 57 years and 66% ( n  = 32) were female. Seventy-six per cent ( n  = 38) of CCEs were complete; however, full colonic views were obtained in 84% ( n  = 42) of cases. Patients > 50 years of age were five times more likely to have an incomplete CCE and there was also a trend towards known comorbidities associated with hypomobility having reduced excretion rates. Overall diagnostic yield for CCE in the unexplored segments was 74% ( n  = 37), with 26% ( n  = 13) of patients requiring significant changes in management based on CCE findings. The overall incremental yield was 38%. CCE findings were normal 26% ( n  = 13), polyps 38% ( n  = 19), inflammation 22% ( n  = 11), diverticular disease 25 ( n  = 12), angiodysplasia 3% ( n  = 1) and cancer 3% ( n  = 1). Significant small bowel findings were found in three (6%) cases, including Crohn's disease and a neuroendocrine tumour. A major adverse event occurred in one patient (2%), related to capsule retention. Conclusion: Same-day CCE is a viable alternative means to assess unexplored segments of the colon after incomplete OC in selected patients.